TEACHER TRAINING: DIVERSIFICATION OF EVALUATIVE INSTRUMENTS CONTRIBUTIONS - Moro Nascimento, Mari Clair [UNESP]; Leite Barbosa, Raquel Lazzari [UNESP]; Borges de Oliveira, Anelise Martinelli [UNESP] (Univ Metodista Piracicaba-unimep, 2017)
This study, that aimed to present the diversity of evaluation instruments as an aspect which may contribute to the formation and performance of future teachers, is based in the qualitative approach and data collected from questionnaire. Information acquired were analyzed, categorized and quantified, on the grounds on content analysis. The observation turns to the evaluation in teacher training courses, because we believe that if student teachers experience the diversity of evaluation tools may expand their knowledge about the status of their own learning and training, making use of this practice when they are in the teaching profession in order to encourage the improvement of students knowledge who will be acting in the context of basic education. The survey was conducted in 2014, in a 2nd year classes in a Faculty of Education whose operation takes place in a public university located in the state of Parana, Brazil. The data enable to realize the portfolio and the conceptual map as the evaluation instruments that provided more learning, as well as the importance of teacher's feedback to students, considering essential the return about the quality of learning.
Keywords: EVALUATION TOOLS; FORMATIVE ASSESSMENT; TEACHER TRAINING